Palliative Care in the Community: A Systematic Review of Integrated Services Combining Radiation Therapy for Pain Relief, Home-Based Nursing, and Family Physician Support - Alaradi , Eman Abdullah; Al Aradi , Zainab Abdullah; Alatawi , Huda Mutir; Alatawi , Shrouq Awad; Alessi , Ali Saleh; Dilyh , Samar Yahya; Al-Eid , Zahra Makki Jaffar; Alqubbi , Ali Muhammad; Dilyh , Nuha Yahya; Al Mohmed , Zahra Abdulkarim (Journal of Ecohumanism, 2024)
Background: Palliative care in the community is increasingly recognized as essential for improving quality of life in patients with advanced illnesses. Integrated services that combine medical, nursing, and psychosocial support aim to provide comprehensive symptom management, particularly for pain, which remains a major concern. Radiation therapy (RT) has a well-established role in alleviating cancer-related pain, yet its integration with home-based nursing and primary care remains underexplored. Objective: This systematic review aimed to evaluate the effectiveness, feasibility, and outcomes of community-based palliative care models that integrate RT for pain relief, home nursing, and family physician support. Methods: A systematic search was conducted across PubMed, Scopus, Web of Science, and Cochrane Library databases for studies published up to 2025. Inclusion criteria comprised studies describing community-based palliative care models that incorporated RT for pain, home nursing interventions, and primary care physician involvement. Outcomes assessed included pain reduction, patient satisfaction, quality of life, hospital admissions, and service feasibility. Data extraction and quality appraisal were performed independently by two reviewers, with discrepancies resolved by consensus. Results: The review included 21 studies encompassing a total of 3,150 patients. Evidence suggests that integrating RT into home-based palliative care, supported by nursing and family physicians, significantly improved pain management and overall patient comfort. Patients experienced reductions in opioid use, fewer emergency visits, and higher satisfaction with care. Home-based nursing facilitated adherence to care plans, monitoring of treatment side effects, and psychosocial support, while family physicians ensured continuity of care and coordination with oncology services. Barriers identified included logistical challenges for RT delivery, limited interdisciplinary communication, and resource constraints. Conclusion: Community-based integrated palliative care models that combine RT for pain relief with home nursing and family physician support are feasible and effective in improving patient-centered outcomes. These models reduce hospital dependency and enhance quality of life, highlighting the importance of multidisciplinary collaboration in community settings. Future research should focus on standardized protocols, cost-effectiveness, and strategies to overcome logistical barriers in delivering RT in the community.